Book Review: Margot Adler's Heretic's Heart - Clifton, Chas S (Pomegranate, 1998)
Margot Adler's story is set in the middle of that over-summarised decade, the 1960s. One advantage to reading it is to get past the image of antiwar protests, burning inner-city neighbourhoods, and LSD and to hear two people's stories: hers and that of the American soldier who became her pen pal, confidant and lover.